2019
DOI: 10.1088/1361-6528/aaf7c8
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O porous nanostructured films fabricated by positive bias sputtering deposition

et al.

Abstract: In this work, the authors fabricated Cu2O porous nanostructured films (PNFs) on glass slide substrates by the newly developed positive bias deposition approach in a balanced magnetron sputtering (MS) system. It was found that the surface morphology, crystal structure and optical property of the as-deposited products were greatly dependent on the applied positive substrate bias. In particular, when the substrate was biased at +50 V and +150 V, both of the as-prepared Cu2O PNFs exhibited a unique triangular pyra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…[25]. In this bias deposition, the tip charging effect [25,26] was demonstrated to dominate the formation process of the PNFs. To investigate the physical and chemical instabilities of the as-prepared Cu2O PNFs, several kinds of heating treatments such as rapid thermal processing (RTP), high vacuum annealing (HVA), dry-oxygen oxidation and wet-oxygen oxidation were respectively carried out at 200-500 ℃ for a duration of 30 min.…”
Section: Methodsmentioning
confidence: 83%
“…[25]. In this bias deposition, the tip charging effect [25,26] was demonstrated to dominate the formation process of the PNFs. To investigate the physical and chemical instabilities of the as-prepared Cu2O PNFs, several kinds of heating treatments such as rapid thermal processing (RTP), high vacuum annealing (HVA), dry-oxygen oxidation and wet-oxygen oxidation were respectively carried out at 200-500 ℃ for a duration of 30 min.…”
Section: Methodsmentioning
confidence: 83%
“…Consequently, the incident Cu atoms will be uniformly attracted by the uniform electrostatic field and finally a uniform, flat and compact CuO thin film is thus formed. Also note that the morphology of CuO thin film deposited on polished Si wafer is greatly different from that of Cu 2 O thin film deposited on glass side at a substrate bias of +50 V [13] although the substrate morphologies are both smooth and flat. This may be attributed to two possible reasons.…”
Section: Resultsmentioning
confidence: 94%
“…The sputtering deposition was carried out at a RF power of 80 W at room temperature and the deposition duration was controlled to be 60 min. The other details and parameters can be found in [13]. It has been demonstrated that the residual O 2 in the pre-pumped vacuum chamber is the main oxygen source for the oxidation of sputtering Cu atoms [15].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations